Management of Lower Urinary Tract Symptoms Attributed to Benign Prostatic Hyperplasia (BPH) - NUMAN ALAM; SYED MUHAMMAD HASSAN AKHTAR; FAISAL; GHULAM MUJTABA; MUHAMMAD SHAHID BHATTI; SAMEER ALI (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Benign Prostatic Hyperplasia (BPH) is a common condition affecting older men, causing lower urinary tract symptoms (LUTS) such as urinary frequency, urgency, weak stream, and nocturia. Aim: To compare the effectiveness of medical versus surgical treatments in managing lower urinary tract symptoms associated with benign prostatic hyperplasia (BPH). Methods This case-control study was conducted at Akber Medical Complex, Mardan during December 2022 to December 2023, involving 255 patients diagnosed with lower urinary tract symptoms attributed to benign prostatic hyperplasia (BPH). Results: Surgical treatment for LUTS due to BPH resulted in greater symptom improvement (47.7% improvement in IPSS) and quality of life (16.2) compared to medical treatment (32.5% and 12.8, respectively). Urinary retentionand post-operative bleeding were more common in the surgical group (8% vs 2% and 5% vs 0%), and hospital stays were longer (5.7 days vs 3.2 days). Both groups showed similar improvements in urinary flow rate. These findings indicate that while surgery provides better symptom relief, medical treatment remains effective with fewer complications and shorter recovery. Conclusion: Both medical and surgical treatments are effective in managing LUTS attributed to BPH, with surgical options offering quicker relief and greater long-term benefits. However, medical treatment remains a viable option for patients who are not candidates for surgery or prefer non-invasive treatment. A personalized approach, considering patient comorbidities and preferences, is essential for optimal management. Keywords: Benign prostatic hyperplasia, UTI, lower urinary tract symptoms